Aspek Pengaruh Naik Turunnya Harga Saham Premier LQ-45 - Isnaini Nur Fadila; Fitrah Sari Islami (Economie: Jurnal Ilmu Ekonomi, 2022)
This study aims to determine the factors thas influence the shelf-decline of stock price in the Indonesia Stock Exchange. To do this writing, the analyst wants to change how the variable interest rate (SBI), kurs and inflation on the share price of primier LQ-45. This research examines the relationship between levels interest rate (SBI), exchange rate, inflation against LQ-45 share price. This study uses the ECM (Error Correction Model) method which begins with a unit root test with the results of the LQ-45 stock price and interest rate (SBI) at the 1st difference level while the exchange rate and inflation are at the level. This study uses secondary data type with a time series January 2015 – December 2020. The result show that in the long and short term the exchange rate has a negative effect on LQ-45 stock prices while inflation has a positive effect on LQ-45 stock price and interest rate have a positive effect on LQ-45 stock price short term while the long term produces a negative effect on the stock price of LQ-45.